Gasket-integrated carbon/silicone elastomer composite bipolar plate for high-temperature PEMFC. (15th September 2015) - Lee, Dongyoung; Lim, Jun Woo; Nam, Soohyun; Choi, Ilbeom; Lee, Dai Gil
Abstract: The primary components of proton exchange membrane fuel cell (PEMFC) systems are bipolar plates, end plates, membrane electrode assemblies (MEAs), gas diffusion layers (GDLs), and gaskets. The PEMFC composed of many components induces sealing problem of the stack, which affects the fuel efficiency, reliability, and maintenance costs of the system. Conventional PEMFCs are sealed with numerous elastomeric gaskets to seal the stack, which increases the manufacturing and assembly costs. To reduce the assembly time and to increase the sealing reliability without the use of gaskets, a gasket-integrated carbon/silicone elastomer composite bipolar plate is developed. Silicone elastomer is employed rather than conventional glassy thermoset or thermoplastic polymers for the matrix of the composite bipolar plate, where the silicone elastomer works as gaskets due to its resilience. The mechanical and electrical properties of the developed carbon/silicone elastomer composite are investigated at both room temperature and operating temperature of high-temperature PEMFCs (HT-PEMFCs). The sealability of the gasket integrated composite bipolar plate is tested.